ANALISIS PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. GROWTH ASIA MEDAN - Simbolon, Sahat (UNIKA Santo Thomas, 2020)
The purpose of this study was to analyze the effect of work motivation and competence on the performance of employees in the production department at PT Growth Asia Medan. The study was conducted on employees of the production section of PT Growth Asia Medan with a population of 320 people. Samples were taken as many as 80 people. Data collection was carried out using questionnaire methods and documentation techniques. Data were analyzed using descriptive methods and multiple linear regression analysis. Partial test results (t test) prove that motivation has a positive but not significant effect on employee performance, while competence has a positive and significant effect on the performance of employees of PT Growth Asia Medan. Simultaneous test (F test) shows that work motivation and competency simultaneously have a significant effect on employee performance. The coefficient of determination (R2) of 0.703 means that 70.3% of the performance of PT Growth Asia Medan's production department employees is influenced by work motivation and employee work competence, while the remaining 29.7% is influenced by other variables not examined in this study, for example leadership variables, commitment work, work culture, work environment, compensation, and so on. Leaders need to pay attention to work performance, giving bonuses, direction, and increasing work motivation for employees